Covert coping with unfair treatment at work and risk of incident myocardial infarction and cardiac death among men: prospective cohort study. Issue 5 (24th November 2009) - Leineweber, C; Westerlund, H; Theorell, T; Kivimäki, M; Westerholm, P; Alfredsson, L
Abstract : Background: Covert coping with unfair treatment at work—occurring when an employee does not show the "aggressor" that he/she feels unfairly treated—has been found to be associated with cardiovascular risk factors. This study examined whether covert coping also predicts incident coronary heart disease. Methods: A prospective cohort study (the WOLF Stockholm study) of workplaces in the Stockholm area, Sweden. The participants were 2755 men with no history of myocardial infarction at baseline screening in 1992–1995. The main outcome measure was hospitalisation due to myocardial infarction or death from ischaemic heart disease until 2003 obtained from national registers (mean follow-up 9.8±0.9 years). Results: Forty-seven participants had myocardial infarction or died from ischaemic heart disease during follow-up. After adjustment for age, socioeconomic factors, risk behaviours, job strain and biological risk factors at baseline, there was a dose–response relationship between covert coping and risk of incident myocardial infarction or cardiac death (p for trend=0.10). Men who frequently used covert coping had a 2.29 (95% CI 1.00 to 5.29) times higher risk than those who did not use coping. Restricting the analysis to direct coping behaviours only strengthened this association (p for trend=0.02). Conclusions: In this study, covert coping is strongly related to increased risk of hard-endpoint cardiovascular disease.